Silylated-montmorillonite as co-adsorbent of chitosan composites for methylene blue dye removal in aqueous solution - Saputra, Ozi Adi; Kurnia; Pujiasih, Septi; Rizki, Vanani Nur; Nurhayati, Betty; Pramono, Edi; Purnawan, Candra (Communications in Science and Technology, 2020)
Industrialization plays important role in the economy of developing countries, including increasing community welfare. However, the presence of poorly industries waste disposal system has negative impact to the environment. Therefore, it is necessary to overcome this problem with low-cost technology, called adsorption. In this research, silylated-montmorillonite (sMMt) has been successfully prepared as supporting material for adsorption of methylene blue by chitosan. The sMMt was characterized by FTIR, XRD, and elemental mapping techniques. The chitosan/sMMt composites were prepared through dissolution-precipitation method and produced rod-like morphology as observed by SEM. The adsorption process was carried out in a batch method by studying the pH and the adsorption contact time. The adsorption kinetic mechanism of the chitosan/sMMt nanocomposite followed pseudo-second order rather than Lagergren model indicating chemisorption predominant. The addition of silylated-montmorillonite into chitosan enhanced the methylene blue dye removal performance, which evidenced by improving Qe values by 10% compared to chitosan.